Influence of grain size on AZO ceramic synthesis - Vera, César Raimundo (2013)
Aluminum doped zinc oxide (AZO) is a transparent conducting oxide (TCO) with oxygen vacancy mediated carrier density and mobility. Due to low oxygen self-diffusivity, the influence of thermal reducing treatments is strongly dependent on grain size. Electrical resistivity and Seebeck coefficient measurements suggest that mobility changes prevail to increase conductivity by reducing atmosphere anneal.